A magyar gazdaságpolitika néhány jellemzője a konvergencia programok és a világgazdasági válság tükrében - Gősi, János (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
According to the Treaty of Maastricht only those member states can join the zone of the common money which meet the so-called requirements of Maastricht of which Hungary has not met even one since our joining the European Union. Besides, up to the autumn 2006 we got away from the time of its introduction planned by 2007. In 2002 fulfilment of requirements regarding inflation seemed to be the most difficult one. In addition it appeared rational to reduce deficiency in the state budget under 3% by 2004. It would have made possible for Hungary to meet the requirements even in the first, so in 2004, convergence programme and after a two year-long period, in 2007 - after the parliamentary election of 2006 - to introduce the euro together with Slovenia.